Efeito da terapia laser de baixa potência em glândulas parótidas de camundongos submetidos à radioterapia - Acauan, Monique Dossena (2015)
Head and neck radiotherapy often involves major salivary glands and causes morphologic and functional alterations, resulting in hyposalivation and xerostomia. Literature was reviewed in the first manuscript, addressing the structural changes observed in the salivary glands resulting from oxidative stress caused by radiotherapy and pathogenic mechanisms involved. Preventive and regenerative therapies for altered acinar morphology and glandular function were also discussed. Among the acute and late microscopic alterations observed in glandular tissue, there are particularly changes indicative of cell death, hypovascularization, formation of fibrous tissue and edema. Considering the evidences before mentioned, the aim of this study was to evaluate the effect of low level laser therapy (LLLT) on radiotherapy-induced morphological changes and immunodetection of caspase-3 protein in parotids of mice. Forty-one Swiss mice were divided into a control group and three experimental groups: radiotherapy, 2 J laser and 4 J laser. The experimental groups were exposed to ionizing radiation in a single session of 10 Gy. In the laser groups, a GaAlAs laser (830 nm, 100 mW, 0.028 cm2, 3.57 W/cm2) was used on the region corresponding to the parotid glands, with 2 J energy (20 sec, 71 J/cm2) or 4 J (40 sec, 135 J/cm2) per point. The animals were euthanized 48 hours or seven days after radiotherapy and parotid glands were dissected for morphological analysis and immunodetection of caspase-3. There was no significant difference between groups in the immunodetection of caspase-3, but the laser groups had a lower percentage compared to the radiotherapy group. Furthermore, the results indicated that LLLT promoted the preservation of acinar structure, reduced the occurrence of cytoplasmic vacuolation and stimulated parotid gland vascularization. Of the two LLLT protocols, the one using 4 J of energy showed better results. Given the methodological limitations of this study, further researches should be conducted in irradiated animals, using different LLLT protocols and observing glandular response, not only in the short term but also long term, when the occurrence of late changes in the salivary glands can be analyzed.